Assessing implementation of veterinary extension on control of cattle parasites, in Moretele district, Northwest Province - McCrindle, Cheryl Myra Ethelwyn (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Sciences))--University of Pretoria, 2004.